Реконструкція маси МССМ бозону Хіггса - Obikhod, T. V.; Petrenko, I. A. (Publishing house "Academperiodika", 2019)
The problems of the Standard Model, as well as questions related to Higgs boson properties led to the need to model the ttH associated production and the Higgs boson decay to a top quark pair within the MSSM model. With the help of computer programs MadGraph, Pythia, and Delphes and using the latest kinematic cuts taken from experimental data obtained at the LHC, we have predicted the masses of MSSM Higgs bosons, A and H.